Structure and reactivity of cyclic imido derivatives of phosphoric acid - Scaillet, Sonia (Department of Chemistry, 2023)
New cyclic 1,3-diazaphospholidine-2,4,5-triones were synthesised and their solvolytic behaviour was studied. Methanolysis of 2-methylamino (24) and 2-dimethylamino (25) derivatives showed evidence of cleavage of both imide P-N bonds. This indicates that the ring opening in these derivatives is much slower than the second P-N cleavage in the ring-opened intermediate (30, scheme 11). On the other hand, methanolysis of 1,3-dimethyl-2-phenoxy-1,3,2-diazaphospholidine-2,4,5-trione (22) yielded the product of the cleavage of only one P-N bond. This product (26, scheme 9) was relatively stable towards further solvolysis. This was taken by Mulliez8 as evidence for the addition-elimination mechanism of solvolysis, since in such a case 22 would experience the usual rate accelerating effect upon the formation of the pv intermediate with trigonal bipyramidal structure. The crystal structures of 24 and 25 were determined in order to investigate the low reactivity of 24 and 25 to solvolysis. This low reactivity correlates with the small size (92.3 and 91.9° respectively) of their endocyclic N-P-N angle. In the case of these two compounds, this suggests that the driving force towards the formation of the pv trigonal bipyramidal intermediate is reduced. Aminolysis of 22 with ammonia and p-anisidine resulted in products which indicate that nucleophilic attack takes place exclusively at the phosphorus atom. In the aminolysis with p-anisidine, both P-0 bond cleavage (displacement of phenol, 43) and ring P-N bond cleavage (44) products were obtained. This can be explained in terms of pseudorotation of the initially formed pv intermediate (22A, scheme 23). The aminolysis of 22 with ammonia yielded exclusively the ring-retained P-OPh bond cleavage product (23). This indicates that pseudorotation of the initially formed pv intermediate (22A, scheme 20) is much faster than endocyclic P-N bond cleavage. Finally,amminolysis of 22 with benzylamine was performed.As reported by Mulliez8, this reaction yielded the product (45) of the initial C-N cleavage, followed by ring closure Acidolysis studies were carried out in anhydrous TFA. These studies indicated that the low reactivity towards nucleophilic attack of 2-amino (23), 2-methylamino (24),2-dimethylamino (25) and 2- p-anisidino (43) derivatives may also be accounted for by the lowered electrophilicity of their phosphorus atom. Finally, within the cyclic 1,3-diazaphospholidine-2,4,5-trione series the reactivity of the various compounds was found to be vastly different, depending on which substituents were present on the exocyclic N atom. Part of the work reported in this thesis has been published; viz.; Phosphoric Carboxylic lmides. Part 6. Structure and Reactivity of 1 ,3,2-diazaphospholidine4,5-diones; Crystal Structure of 1,3-Dimethyl-2-methylamino-1,3,2-diazaphospholidine-2,4,5- trione,Alan T. Hutton, Tomasz A. Modro, Margaret L. Niven, and Sonia Scaillet, J. Chem. Soc. Perkin Trans. II, 17 (1986).